Antidumping Investigations and the Pass-Through of Antidumping Duties and Exchange Rates - Blonigen, Bruce A; Haynes, Stephen E (American Economic Review, 2002)
Antidumping Investigations and the Pass-Through of Antidumping Duties and Exchange Rates by Bruce A. Blonigen and Stephen E. Haynes. Published in volume 92, issue 4, pages 1044-1061 of American Economic Review, September 2002